Body Fat Percentage, Waist Circumference and Body Mass Index are Correlated with Nitric Oxide Levels in Young Adults with Central Obesity - Feriyandi Nauli; Nurhasanah Nurhasanah; Endang Mahati; Udin Bahrudin (Molecular and Cellular Biomedical Sciences, 2021)
Background: Central obesity stands for the corner-stone of cardio-metabolic health, while nitric oxide (NO) is a major regulator of cardiovascular function. To day, the correlation between serum NO metabolites nitrate/nitrite and the obesity components in young adults remains elusive. Thus, this current study was conducted to know the correlation between serum NO metabolites levels and body fat percentage, waist circumference (WC) as well as body mass index (BMI) in young adults with central obesity.Materials and Methods: A cross-sectional study was conducted in Riau, Indonesia, involving 79 young adults aged 18-25 years, composing of 39 and 40 subjects with and without central obesity, respectively. Anthropometric measurements were performed to assess WC and BMI. Body fat percentage was measured using bioelectrical impedance analysis and serum NO metabolites levels were assessed using Griess methods.Results: Levels of serum NO metabolites were significant higher in the subjects with central obesity (168.41±12.64 μmol/L) than that of normal subjects (70.57±44.99 μmol/L, p<0.001), but the levels were no significant different between male and female subjects. Serum NO metabolites levels were strongly correlated with total body fat (r=0.618, p<0.001), visceral fat (r=0.733, p<0.001), subcutaneous fat (r=0.547, p<0.001), WC (r=0.717, p<0.001) and BMI (r=0.788, p<0.001).Conclusions: For young adults in Riau, Indonesia, levels of serum NO metabolites are higher in the central obesity group than that of the normal. In this population, body fat percentage, waist circumference and body mass index are correlated with serum nitric oxide metabolites levels.Keywords: nitric oxide, body fat percentage, young adults, central obesity